1993
DOI: 10.1148/radiographics.13.6.8290724
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler US of children with acute lower abdominal pain.

Abstract: The authors review the color Doppler ultrasonographic (US) features of appendicitis and other diseases that can manifest with acute lower abdominal pain. Causes of acute abdominal pain, other than appendicitis, include gynecologic abnormalities (ovarian cyst, ovarian torsion, pelvic inflammatory disease), gastrointestinal abnormalities (infectious enteritis, Crohn disease, mesenteric lymphadenitis, intussusception), and urinary tract diseases. On color Doppler images, inflammatory and infectious processes usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 0 publications
0
15
0
3
Order By: Relevance
“…7) [5,9]. Color Doppler examination can show an increase of vascularity of the appendiceal wall in the first stage and loss of vascularity in the later stage [3]. Failure to identify the appendix by US or identification of a normal appendix less than 6 mm in diameter makes the diagnosis of appendicitis very unlikely.…”
Section: Acute Appendicitismentioning
confidence: 99%
See 3 more Smart Citations
“…7) [5,9]. Color Doppler examination can show an increase of vascularity of the appendiceal wall in the first stage and loss of vascularity in the later stage [3]. Failure to identify the appendix by US or identification of a normal appendix less than 6 mm in diameter makes the diagnosis of appendicitis very unlikely.…”
Section: Acute Appendicitismentioning
confidence: 99%
“…Differential diagnoses include: Crohn's disease, ovarian pathologies, mesenteric adenitis, nephrolithiasis and Meckel's diverticulitis (Fig. 8) [1,3,6,7,10]. Mesenteric adenitis…”
Section: Acute Appendicitismentioning
confidence: 99%
See 2 more Smart Citations
“…The first studies in children were performed by Quillin and Siege [29,30] that noted that in the color Doppler can differentiate extrinsic causes of intestinal disease, such as peritonitis, to primary intestinal processes and identify different locations compromised. Several authors have suggested US as the first study to be conducted in the diagnostic investigation process of suspected inflammatory bowel disease [13,[31][32][33].…”
Section: Gray Scale and Color Doppler Ultrasoundmentioning
confidence: 99%